2007
DOI: 10.1016/j.neuro.2006.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic tremor: Differences between smokers and non-smokers

Abstract: Tremor is among the acute effects of nicotine exposure. Published studies have focused on smokingrelated postural (static) hand tremor rather than kinetic tremor (tremor during hand use), and gender differences in smoking-related tremor have not been examined. In a group of adults who were sampled from a population (mean ± SD = 65.7 ± 11.5 years, range = 18 -92 years), the investigator assessed whether the severity of postural and kinetic tremors differed in smokers versus non-smokers, and whether this differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 26 publications
2
25
1
Order By: Relevance
“…We found that tremor scores in the left hand were higher than those in the right (usually dominant) hand. A study of 273 normal adults in New York similarly reported that tremor scores in the left hand were higher than those in the right hand [16] . Motor control, in general, is superior in the dominant than non-dominant arm, and this is one possible explanation.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We found that tremor scores in the left hand were higher than those in the right (usually dominant) hand. A study of 273 normal adults in New York similarly reported that tremor scores in the left hand were higher than those in the right hand [16] . Motor control, in general, is superior in the dominant than non-dominant arm, and this is one possible explanation.…”
Section: Discussionmentioning
confidence: 98%
“…Having rigidly fixed task goals places more pressure on the subject, which worsens their tremor [15] . Also, tremor on spirals was previously rated in a study of 273 normal adults in New York [16] but these results are difficult to compare again because spirals were drawn free-hand and furthermore, a rating of 0.5 was not used in that study, which likely resulted in lower tremor scores in that study. The other possibility, alluded to above, is that tremor may indeed be more common in children than previously suspected and this could be an additional feature of an immature motor-coordination/ cerebellar system.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nicotine is believed to act by binding the nico- tinic cholinergic receptors in skeleton muscle. [12][13][14] This study was not designed to capture the acute effects of smoking; tremor was not measured in smokers immediately after they smoked a cigarette. The interest of our study was the nonacute effects of smoking on the frequency of hand tremor.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that tobacco smoking increased tremor. [12][13][14] Some studies reported an inverse association between smoking and Parkinson disease (PD). [15][16][17] We are interested in differentiating the hand tremor in smokers from that in Parkinsonism.…”
mentioning
confidence: 99%